Recent advances in immunoassay-based mycotoxin analysis and toxicogenomic technologies - Liew, Winnie-Pui-Pui (The Journal of Food and Drug Analysis (JFDA), Food and Drug Administration, Taiwan (TFDA), 2022)
The co-occurrence and accumulation of mycotoxin in food and feed constitutes a major issue to food safety, food security, and public health. Accurate and sensitive mycotoxins analysis can avoid toxin contamination as well as reduce food wastage caused by false positive results. This mini review focuses on the recent advance in detection methods for multiple mycotoxins, which mainly depends on immunoassay technologies. Advance immunoassay technologies integrated in mycotoxin analysis enable simultaneous detection of multiple mycotoxins and enhance the outcomes’ quality. It highlights toxicogenomic as novel approach for hazard assessment by utilizing computational methods to map molecular events and biological processes. Indeed, toxicogenomic is a powerful tool to understand health effects from mycotoxin exposure as it offers insight on the mechanisms by which mycotoxins exposures cause diseases.